ennel, Carob, Rosemary Extracts as AntiInflammatory Activity Functions on Formalin Induced Paw Edema in Albino Rats - Nasra, A. Abd-Elhak; Hanaa, S. M. Abd El-Rahman; Mahmoud, A.M. Saleh (Food Technology Research Journal, 2024)
Inflammation and oxidative stress are features of many degenerative illnesses. In this study, the anti-inflammatory and antioxidant effects of fennel fruits (Foeniculum vulgare), carob (Ceratonia siliqua L), and rosemary (Rosmarinus officinalis L) aqueous extracts were investigated in vivo. Two models of formalin-induced paw edema were used to investigate the anti-inflammatory impact. The rat was given a formalin injection to cause an inflammatory process resulting in edema in the right leg. Formalin at 2.5% and 10% concentrations resulted in rat paw edema. In the anti-inflammatory study, Group 1: Normal control; no induced inflammation. Positive control (group 2) was given formalin. Rats were administered 200 and 400 mg/kg b.w. of fennel extract to groups 3 and 4. Rats given formalin received carob extracts at dosages of 400 and 800 mg/kg. in Groups 5 and 6. Groups 7, 8: Formalin-treated rats were given 400 mg/kg b.w. and 200 mg/kg. of rosemary extracts. Group 9 includes rats administered formalin plus indomethacin at a dose of 10 mg/kg. In the two experimental formalin models (A and B), aqueous extracts and the standard drug were administered orally through a gastric tube 30 minutes after the formalin injection in the right hind of the rat paw. Following the 15-day trial period, blood and tissue samples were taken, and histopathological and biochemical parameter analyses were done. According to research, these plant aqueous extracts effectively reduce inflammation in rat paw edema caused by formalin.